2012
DOI: 10.1080/15534510.2012.712548
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of behavioral norms related to HIV transmission by people with HIV and by residents of their communities

Abstract: We examined how people with HIV are both part of and apart from the communities in which they live. We compared perceptions of behavioral norms of 203 people with HIV living in 33 different communities with community-level normative perceptions assessed by surveys of 2,444 randomly selected residents of these communities. Participants with HIV perceived behavior that risks the transmission of HIV as injunctively and descriptively more normative than did other community residents. Participants with HIV living i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…They were recruited as part of a larger project (Miller, Bunn, Grover, & Solomon, 2014: Miller, Grover, Bunn, & Solomon, 2011; Varni, Miller, McCuin, & Solomon, 2012; Varni, Miller, & Solomon, 2012). ) that involved extensive assessment of HIV stigma as it is experienced by men and women with HIV in rural New England, and as it is expressed by the communities in which they live (Miller, Bunn, Grover, & Solomon, 2014: Miller, Grover, Bunn, & Solomon, 2011; Varni, Miller, McCuin, & Solomon, 2012; Varni, Miller, & Solomon, 2012). Data from three male participants were not recorded due to computer errors, and five men did not answer questions about their sexual behavior.…”
Section: Methodsmentioning
confidence: 99%
“…They were recruited as part of a larger project (Miller, Bunn, Grover, & Solomon, 2014: Miller, Grover, Bunn, & Solomon, 2011; Varni, Miller, McCuin, & Solomon, 2012; Varni, Miller, & Solomon, 2012). ) that involved extensive assessment of HIV stigma as it is experienced by men and women with HIV in rural New England, and as it is expressed by the communities in which they live (Miller, Bunn, Grover, & Solomon, 2014: Miller, Grover, Bunn, & Solomon, 2011; Varni, Miller, McCuin, & Solomon, 2012; Varni, Miller, & Solomon, 2012). Data from three male participants were not recorded due to computer errors, and five men did not answer questions about their sexual behavior.…”
Section: Methodsmentioning
confidence: 99%
“…In general, these adverse effects are expected to operate whether the stigmatized condition is visible (eg, race/ethnicity) or concealable (eg, asymptomatic HIV) [ 23 , 24 ]. Several studies have also examined the health and behavioral impacts of social norms [ 25 - 31 ], but few studies in the literature on HIV stigma have directly connected the two constructs [ 29 , 32 , 33 ]. In a well-designed US study of persons with concealable stigmatized identities such as mental illness and family health problems, Quinn and Chaudoir [ 17 ] examined how both anticipated stigma and social norms (described in their article as “cultural stigma”) were associated with psychological distress.…”
mentioning
confidence: 99%
“…The study in the literature most similar to ours is a study of persons with HIV in which their individual assessments were geographically linked to population-based surveys of randomly selected residents of those same US communities [ 32 , 33 ]. That study–similar in design to Quinn and Chaudoir [ 17 ] and Hargreaves and colleagues [ 34 ] in its linkage of data between focal study participants (ie, those with the stigmatized condition) and an independent sample of community-dwelling individuals–found that the association between community norms about condom use for HIV prevention and HIV-positive participants’ concern with public attitudes was mediated by HIV-positive participants’ perceptions of the norm [ 33 ].…”
mentioning
confidence: 99%